DIALECT USE IN ARABIC ALGERIAN LITERATURE, THE CASE OF RIH EL DJANOUB BY ABD EL HAMID BENHADOUGA - Benheddi, Karima (PEOPLE: International Journal of Social Sciences, 2017)
The present research paper is an attempt to analyse the role of dialect use in literature, as dialect use in literature has long been rejected by various authors and speakers all over the world; considering it as a symbol of under development. Fortunately literary dialect has struggled to maintain its place since it captured the interest of dialectology, sociolinguistics and literature. Thus, it is meant to transfer information about inner and outside world. Rih El Djanoub is not chosen randomly but on purpose because the novel is considered as a speech community and it is also affected by social variables (age, gender, social context and cultural background). Based on a set of literary (the novel of Rih El Djanoub as a field of work), linguistic (phonological and morphological levels) and sociolinguistic (social variables) approaches) - so, these approaches are used to analyse the discourse analysis in the novel. The available cultural and linguistic data in the novel have been analysed and interpreted in order to come up with the following findings: what characterizes Benhadouga’s novel and supplies it with distinguished glamour is the presence of language diversity so, despite the standard form is the dominant variety in the novel but, when the author is exposed to cultural elements such as: proverbs, popular songs, games and folk beliefs, he used dialect in order to be faithful to the context by retaining the original words of characters in dialogue. This work aims to raise dialect awareness among readers and to capture the post independent Algerian era. Moreover, to pave the roads for other research works about literary dialect.